The Influence of Price Fluctuations and Availability of Soybean Raw Materials on Tempe Home Industry Production Results in Mataram City - Apriliani, Ayu; Pusparini, Herlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the influence of price fluctuations and the availability of soybean raw materials on tempe production in Mataram City. This research uses primary data through interview and observation techniques guided by questionnaires to tempe home industry entrepreneurs in Mataram City. Determining the selected sample locations using a purposive sampling technique and taking the number of tempe home industry samples using proportional purpose sampling with a total sample of 40 tempe home industries. Next, data processing uses the SPSS 26 application. Based on the results of research data, price fluctuations do not affect tempeh production results. Meanwhile, the availability of raw materials influences tempeh production results.